2021
DOI: 10.1080/10494820.2021.1950772
|View full text |Cite
|
Sign up to set email alerts
|

How collaboration influences the effect of note-taking on writing performance and recall of contents

Abstract: Note-taking is a commonly applied pedagogical strategy across all areas of education. In higher education specifically, there has been an increasing push to get students involved in collaborative note-taking in order to increase their engagement with the contents and to inspire deeper and more meaningful learning. However, there is a lack of clarity as to whether collaborative note-taking positively influences student performance. For this reason, the present study (n = 189) compares the learning performances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…instead of an experimental one because the primary aim is to better understand the effects of encoding on storage and learning performance when taking collaborative notes rather than to compare the effects of individual versus collaborative note-taking, which my coauthors and I have already done in prior studies (Courtney, Costley, Baldwin et al, 2022;Fanguy, Baldwin, Shmeleva et al, 2021). In the present study, I wish to measure specific collaborative encoding behaviors to better understand their effects on the quality of notes produced and the learning performance of groups and their constituent members.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…instead of an experimental one because the primary aim is to better understand the effects of encoding on storage and learning performance when taking collaborative notes rather than to compare the effects of individual versus collaborative note-taking, which my coauthors and I have already done in prior studies (Courtney, Costley, Baldwin et al, 2022;Fanguy, Baldwin, Shmeleva et al, 2021). In the present study, I wish to measure specific collaborative encoding behaviors to better understand their effects on the quality of notes produced and the learning performance of groups and their constituent members.…”
Section: Methodsmentioning
confidence: 99%
“…While most of the research on note-taking examines contexts where notes are taken by a single learner, recent advances in cloud computing enable multiple students to take notes together in a shared online document. Research on online collaborative note-taking is still in its infancy, although a number of studies have shown benefits to this practice, including higher grades (Orndorff, 2015) and improved recall (Fanguy, Baldwin, Shmeleva et al, 2021). Although the cognitivist viewpoint that underpins the encoding-storage paradigm offers a useful explanation of the mechanisms by which individuals process and store information when writing notes collaboratively, none of the studies on online collaborative note-taking have examined the effects of such learning activities through the encoding-storage paradigm.…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…This is essential for improved student experiences, academic success, and retention rates [1]. In higher education, significant efforts have been made to involve students in collaborative notetaking and boost their engagement with the material for more substantial and expressive learning [2]. Distance learning reduces social connection, student well-being, and studentteacher engagement in general.…”
Section: Introductionmentioning
confidence: 99%